Modeling and Simulation of Fuzzy Logic based Maximum Power Point Tracking (MPPT) for PV Application - Ahmad Saudi Samosir; Herri Gusmedi; Sri Purwiyanti; Endah Komalasari (Institute of Advanced Engineering and Science, 2018)
This paper presents modeling and simulation of maximum power point tracking (MPPT) used in solar PV power systems. The Fuzzy logic algorithm is used to minimize the error between the actual power and the estimated maximum power. The simulation model was developed and tested to investigate the effectiveness of the proposed MPPT controller. MATLAB Simulink was employed for simulation studies. The proposed system was simulated and tested successfully on a photovoltaic solar panel model. The Fuzzy logic algorithm succesfully tracking the MPPs and performs precise control under rapidly changing atmospheric conditions. Simulation results indicate the feasibility and improved functionality of the system.